The Elementary Forms of Petro-Life (Towards Transforming Rentierism and Rentier State Literature) - Sajjad Sattari (دولت‌پژوهی, 2015)
The author formulates "Hydrocarbonism" (as an alternative to the rentierism and rentier state theories) and proposes a set of new concepts such as "Hydrocarbon Man, Hydrocarbon Society, Hydrocarbon Mode of Production, Quasi-Market, Middle Eastern State of Nature, Middle Eastern Social Contract, Middle Eastern Social State, Welfare Technocracy, Rent Wishing Syndrome, Social-X-Factor, and Tax Leviathan". By proposing this new framework in the political economy and political sociology of the Middle East, he intends to answer the fundamental question of "How should we understand the nature and procedure (or modus operandi) of Middle East petro-societies and the elementary forms of life inside them?" The author has five interrelated arguments:First: "Tradition, oil and quasi-market" are a coherent whole and the main source of transition in the Middle East petro-societies from a "hydraulic mode of production" in the pre-capitalist era to a "hydrocarbon mode of production" in the 20th century. These three inseparable sources, more than any other factor, have influenced the life of the mind and living experience of man in the Middle East petro-societies and have given these societies a special content, with special values and special internal dynamics.Second: The endless unity of "tradition, oil and quasi-market" can be assumed as a "Middle Eastern State of Nature" which underlies establishment of a "Welfare Technocracy" (bold or pale) in these hydrocarbon societies. The power elites continuously utilize this welfare technocracy to purchase political goods from social markets and, as a result, constantly manipulate and distort "income, consumption and political life" in these societies.Third: The result of this "Middle Eastern State of Nature" is the passivity of hydrocarbon man and the reproduction of established paradigms of power in these societies. Therefore, the power elites consistently strive to preserve and perpetuate this special state of nature by using welfare technocracy.Fourth: However, welfare technocracy is not able to continuously produce the "Social-X-Factor" (or hope, respect, and trust in these hydrocarbon societies) and, consequently, leads to the expansion of alienation, the gradual decline of all forms of capital, and finally, the impossibility of "economic growth at the same time as deep-rooted political development" in the Middle East hydrocarbon societies.Fifth: Moving towards a "New Middle Eastern Social Contract" and establishing a "Tax Leviathan" is a prerequisite for the slow, difficult, and complex transition of these hydrocarbon societies from their specific state of nature to their special social state.Based on these five arguments, the author focuses on the Middle East hydrocarbon societies in their distinct historical existence and their social context. In this framework, he reconstructs the life of the mind and living experience of hydrocarbon man through empathetic experience with him.Accordingly, in the first section, while criticizing the reductionist nature of rentierism and rentier state theories, the author formulates "Hydrocarbonism" as an alternative theory. In the second section, he defines the hydrocarbon man and society and hydrocarbon mode of production and explains the historical process of constructing Hydrocarbonism in the Middle East petro-societies. In the third section, the author focuses on the nature and causes of permanent unity and alloy-type mixture of "tradition, oil and quasi-market" and describes how to turn it to a "state of nature" in the Middle East hydrocarbon societies. In the fourth section, he explains the internal logic of establishing welfare technocracy and its instrumental nature in the Middle East hydrocarbon societies. In the fifth section, the author elaborates on the passivity of hydrocarbon man due to his simultaneous weaknesses and benefits. In the sixth section, he describes the life of mind and living experience of man in the Middle East hydrocarbon societies. In the seventh section, the author highlights the inherent contradictions of these societies and finally, he emphasizes the necessity of moving towards a "new Middle Eastern social contract" and establishing a "tax Leviathan" in the Middle East hydrocarbon societies.